Calyptocephalella (Anura, Australobatrachia) remains from Río Santa Cruz (Early-Middle Miocene, Santa Cruz Formation), Santa Cruz Province, Argentina - Muzzopappa, Paula (2019)
In this contribution, the first anuran fossils from classical Santacrucian localities of the Río Santa Cruz are described. According to proportions and features recognized in the few skull elements recorded, the remains are assigned to the southern gondwanan Calyptocephalella cf. canqueli. This identification extends geographically the distribution of the fossil taxon, defining this species to be a conspicuous component of the aquatic environments of the warm temperate climatic biotas during the late Oligocene-early Miocene times of Patagonia.